Review of indigenous knowledge in Uganda: implications for its promotion - Tabuti, John R.S.; Van Damme, Patrick (Afrika focus, 2012)
Indigenous knowledge (IK) is an important resource that contributes to social and economic needs, community sustainability and sustainable development (Broadhead & Howard, 2on). IK holders use it to exploit, manage and conserve their environments. In Uganda, a wide diversity of IK exists such as that associated with traditional medicine. However, IK is undergoing rapid change and is weakening because of factors that include the outside influence of western cultures and inadequate documentation. These issues are explored here. Specifically we review the role of IK for household and community well-being, discuss the weakening of IK and describe opportunities in the existing national legal and institutional structures for valorizing IK.
Keywords: Traditional knowledge; Conservation; Traditional medicine; Ethnobotany